Trust and racial income inequality: Evidence from the U.S. - Andrea Tesei (Queen Mary University of London, School of Economics and Finance, 2015)
Existing studies of trust formation in U.S. metropolitan areas have found that trust is lower when there is more income inequality and greater racial fragmentation. I add to this literature by examining the role of income inequality between racial groups (racial income inequality). I find that greater racial income inequality reduces trust. Also, racial fragmentation is no longer a significant determinant of trust once racial income inequality is accounted for. I also show that racial income inequality has a more detrimental effect in more racially fragmented communities and that trust falls more in minority groups when racial income inequality increases. The results hold under both least squares and instrumental variable estimation.
Keywords: D31; Z10; J15; 330; Trust; Racial income inequality; U.S.